2008
DOI: 10.1002/pssb.200879537
|View full text |Cite
|
Sign up to set email alerts
|

Nonprecious metal catalysts for the molecular oxygen‐reduction reaction

Abstract: This review covers the electrocatalytic activities, the corresponding influence factors and the synthesis methods of nonprecious‐metal electrocatalysts towards oxygen‐reduction reaction (ORR) for fuel‐cell systems. In particular, the chalcogenides and the macrocycles containing Co or Fe metals have been focused upon. Due to the scarcity of Pt metal, the Co‐ and Fe‐based chalcogenides are potentially interesting substitutes of Pt although they still show lower catalytic activities for ORR and lower electrochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
112
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 182 publications
(114 citation statements)
references
References 134 publications
(111 reference statements)
0
112
1
1
Order By: Relevance
“…The obtained catalyst were named as catalyst and denoted as ILCFe-HT (HT-heat treated at 1000 o C) and ILC-Fe+Co-HT, respectively. (2)To reduce the synthesizing steps of transition metals promoted to the ILCs, the transition metals (Fe and Fe+Co 1.5% Wt%) were dissolved together with the ionic liquid and were sonicated/stirred for 3 hs, were impregnated into the SBA-15 silica template, and all the samples were carbonized at in N 2 at 900 o C for 3 hs. The ILCs were obtained by dissolving the silica template in 1 M sodium hydroxide aqueous solution at 90 °C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The obtained catalyst were named as catalyst and denoted as ILCFe-HT (HT-heat treated at 1000 o C) and ILC-Fe+Co-HT, respectively. (2)To reduce the synthesizing steps of transition metals promoted to the ILCs, the transition metals (Fe and Fe+Co 1.5% Wt%) were dissolved together with the ionic liquid and were sonicated/stirred for 3 hs, were impregnated into the SBA-15 silica template, and all the samples were carbonized at in N 2 at 900 o C for 3 hs. The ILCs were obtained by dissolving the silica template in 1 M sodium hydroxide aqueous solution at 90 °C.…”
Section: Methodsmentioning
confidence: 99%
“…The full with at half maximum values was fixed at a maximum limit ing type of cathode catalyst due to the high ORR activity, good stability, easy synthesis process, inexpensiveness, and large variety of applications [4]. Among them, ordered mesoporous materials (OMC) have received enormous attention owing to their remarkable functional properties such as high surface area, regular frameworks, and tunable pore sizes with narrow pore size distribution, which makes it suitable for multiple potential applications in catalysis, adsorbents, sensor, electrode materials and energy storage devices [1][2][3][4]. These OMCs can be additionally doped by heteroatoms like nitrogen, which produce an excellent blend and can be very effective for largely enhancing their electro catalytic property [5][6][7][8].…”
Section: Characterization Of Ilsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, a recent study on chalcogen-free RuNx chelate compounds [218,219] has demonstrated comparable catalytic activity and selectivity to Pt-based catalysts for four-electron oxygen reduction in acidic media. Detailed reviews on non-noble metal ORR catalysts are reported [220,221].…”
Section: Non-noble Metal Catalystsmentioning
confidence: 99%
“…In recent years, some promising non-precious catalysts have been developed towards oxygen reduction reaction, including Co or Fe-based macrocyclic compounds 17 , transitional metal chalcogenides 18 , nitrogen-doped carbon nanotubes 19 , nitrogen-doped ordered mesoporous carbon 20 , and even nitrogen-doped graphene 21,22 . The transition metal nitride catalysts also displayed methanol-tolerance for ORR reactions.…”
mentioning
confidence: 99%